Less invasive surgery for cervical spine - Takayasu, Masakazu (Brain and nerve = Shinkei kenkyū no shinpo, 2009)
One of the currently most important subjects in the field of surgical treatment is the development of less invasiveness techniques, which includes those involving small openings with minimal skin incision, less pain, better preservation of function, less restriction of postoperative activities of daily livings (ADLs), early return to social activities, and so on. In surgery of the cervical spine, less pain and less restriction of postoperative ADLs seem to be more important for less invasive surgery than the size of openings or skin incisions because they are already small enough. This paper introduces less invasive methods for the cervical spine, such as the transvertebral key-hole foraminotomy for surgery via the anterior cervical approach and the spinous process-splitting expansive laminoplasty for surgery via the posterior cervical approach. The best method should be selected depending on the needs of each patient.